Adulescens amator? Ethos and humorousness in Pamphilus’ discursive construction in Terence’s Hecyra (Circe de clásicos y modernos, 2020)
Although being an amator is a feature that defines the adulescens from the point of view of palliata’s code, the present paper argues that part of the humorousness of this character comes from the fact that this is a routine that Pamphilus develops only at a discursive level, which does not correspond to his actions on the stage. A second aspect of his humorousness is based on not being the palliata’s typical indecisive adulescens, since, paradoxically, with his decision to avoid acting, he ends up playing the lead role in the plot development.
Keywords: Terencio; Hecyra; Pamphilus; adulescens amator; humorousness